SYSTEMATIC LITERATURE REVIEW PENGEMBANGAN BAHAN AJAR TECHNOPRENEURSHIP - Akhiruddin Pulungan; Jhon V eri (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Technopreneurship is something that really needs to be mastered in this day and age, this research aims to find out the comparison between various summarized journals which discuss Technopreneurship Teaching Material Development material in the Research Question (RQ). The method used in this research is System Literature Review (SLR), which works by taking several scientific articles that match the criteria for the research topic being studied. Articles were taken via Google Scholar between the publication years 2019-2024, where four scientific articles were obtained that were relevant to the research topic discussed. Then the four scientific articles were explained and method mapping was carried out, where the explanation was for RQ1, the methods used included: Qualitative Descriptive, Research and Development, Class Action Method and Research and Development Method, then for RQ2 the explanation was very influential because teaching materials were a supporting factor. in making it easier to understand entrepreneurship material.